The Impact of Osteoporosis on Facet Joint Denervation Treatment Outcomes in Patients with Lumbar Facet Joint Syndrome - Samet Sancar Kaya; Müge Baran (Galenos Yayinevi, 2024)
Objective: The aim of this study was to investigate the effect of osteoporosis (OP) on the outcomes of facet medial branch radiofrequency thermocoagulation (RFT). Materials and Methods: Thirty-six patients with chronic lower back pain due to lumbar facet joint syndrome (LFJS) who underwent facet medial branch RFT were retrospectively reviewed. The patients were divided into two groups: Group I (without OP, n=19) and group II (with OP, n=16). Pre-intervention and post-intervention evaluations of the patients were assessed at 1, 6, and 12th months by visual analog scale (VAS). Results: In both groups, VAS scores 1st, 6th, and 12th months after intervention were lower than those at baseline (p=0.001). There were no significant difference between the groups in terms of VAS score improvement. Conclusion: Lumbar facet medial branch RFT is an effective and safe treatment method in both the short and long-term in patients with LFJS. OP therapy had no effect on RFT treatment results.